2017
DOI: 10.1097/ogx.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence to Guide Ectopic Pregnancy Diagnosis and Management

Abstract: While serial serum human chorionic gonadotropin levels and transvaginal ultrasound are the mainstays of ectopic pregnancy diagnosis, recent publications revisit the utility of endometrial sampling in diagnosing pregnancy location, using manual vacuum aspiration instead of the criterion-standard dilation and curettage. Expectant management of ectopic pregnancies is the subject of ongoing research, and in the meantime, treatment remains medical or surgical (dependent on clinical parameters and patient preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
14

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 55 publications
1
65
0
14
Order By: Relevance
“…3,4 The early diagnosis of this entity is a priority to initiate adequate management and provide the patient with a lower risk of morbidity as far as radical surgical treatment is concerned. 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The early diagnosis of this entity is a priority to initiate adequate management and provide the patient with a lower risk of morbidity as far as radical surgical treatment is concerned. 1…”
Section: Discussionmentioning
confidence: 99%
“…It occurs when the zygote is implanted in the path of the cervical canal. 1,2 It is an exceptional entity, corresponding to less than 1% of ectopic pregnancies. With an incidence calculated at 1:2500 to 1:12,000 pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of hCG, specifically the beta isoform (βhCG), is a well‐established diagnostic tool for the detection of early pregnancy, but also an important marker of the viable pregnancy 3 . Moreover, levels of βhCG, together with the absence of ultrasonographic signs of the intrauterine pregnancy, are indicative of the pregnancy of the unknown origin (PUO), especially the ectopic, tubar pregnancy 3,4 . It has also been reported that the levels of βhCG in the cases of PUO are often above discriminatory levels, while the initial rise of the βhCG in the first few days is less than 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pregnancy is a common cause of maternal death, accounting for 10% of maternal deaths. In recent years, its incidence has increased [2][3] . Although traditional salpingectomy is a reliable treatment approach, it is likely to reduce the fertility of patients.…”
Section: Discussionmentioning
confidence: 99%